He said, she said: Autism spectrum diagnosis and gender differentially affect relationships between executive functions and social communication - Gallagher, Louise (My University, 2019)
Autism spectrum disorder is characterized by difficulties with social communication, with a preponderance in males. Evidence supports a relationship between metacognitive executive functions (e.g. planning, working memory) and social communication in autism spectrum disorder, yet relationships with specific metacognitive executive functions and how gender alters the expression of these relationships require further study. We used multiple regression to examine relationships between informant-based measures of metacognitive executive function and social communication in intellectually able (IQ ⩾ 85) female (n = 111; mean age = 10.2 ±2.8; 31 autism spectrum disorder) and male youth (n = 310; mean age = 10.5 ±1.9; 146 autism spectrum disorder) with and without autism spectrum disorder from the Autism Brain Imaging Data Exchange-II database. Executive function–social communication relationships were different in females and males with autism spectrum disorder. Relationships between the entire metacognitive index and social communication were stronger in males with autism spectrum disorder than without; this pattern was also observed for metacognitive sub-indices ‘monitor’ and ‘working memory’. These patterns were not observed in females. Relationships between executive function and social communication appear different for female and male youth with an autism spectrum disorder diagnosis. To better understand the nature of metacognitive contributions to social communication in autism spectrum disorder, future work should investigate the co-development of monitoring, working memory and social communication, while taking gender into account.
PUBLISHED
Keywords: Autism; Executive functions; Metacognition; Social communication; Working memory